Physical Parameters of Polymer Composite Materials Created on the Basis of Low and High Molecular Weight Rubbers (Fracture and Structural Integrity, 2020)
ABSTRACT. The theoretical foundations of the structural and mechanical behavior of filled three-dimensional cross-linked elastomers are supplemented. Numerical experiments are carried out, based on the data of numerical experiments, three dimensional cross linked, filled with dispersed particles frost-resistant elastomers based on low and high molecular weight rubbers are developed. Theoretical and experimental data are compared and their good convergence is shown. Comparison of the physical parameters of the composites created by the authors on the basis of low and high molecular weight rubbers showed that the deformation characteristics of the composite based on high molecular weight rubbers are many times superior to composites based on low molecular weight, as well as their glass transition temperature is also very different. The created composites are recommended as a structural material in relation to the engineering problem of creating wear-resistant parts and components of road and air transport operated in a wide temperature range, including the Far North and the Arctic.
Keywords: Deformation; Mechanical stress; Filler; High molecular weight rubber; Low molecular weight rubber; Fracture energy